1983
DOI: 10.3758/bf03199643
|View full text |Cite
|
Sign up to set email alerts
|

Biological constraints on instrumental and classical conditioning: Retrospect and prospect

Abstract: The adequacy of traditional approaches to the study of animal learning to account fully for learning phenomena has been seriously questioned during the past decade. Critics of traditional analyses advocated a biological orientation to the interpretation of associative processes and introduced a variety of concepts intended to provide a new framework for the study of animal learning. This promise of a reorientation of the field has not been realized. The concepts of biological constraints, adaptive specializati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(95 citation statements)
references
References 52 publications
2
93
0
Order By: Relevance
“…Domjan and Galef (1983), for example, outlined a strategy that includes, first, the identification of different selective pressures acting on phylogenetically similar forms; second, the formation of hypotheses concerning different associative processes likely to stem from the observed selective pressures; and third, demonstration of a correlation between behavioral elaborations and selective pressures. (Note that by observing the first two steps, the commonly observed ex post facto nature that frequently characterizes theorizing about the phylogeny of target behaviors is avoided.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domjan and Galef (1983), for example, outlined a strategy that includes, first, the identification of different selective pressures acting on phylogenetically similar forms; second, the formation of hypotheses concerning different associative processes likely to stem from the observed selective pressures; and third, demonstration of a correlation between behavioral elaborations and selective pressures. (Note that by observing the first two steps, the commonly observed ex post facto nature that frequently characterizes theorizing about the phylogeny of target behaviors is avoided.)…”
Section: Discussionmentioning
confidence: 99%
“…Research in this area has often been placed in broader theoretical contexts such as preparedness, belongingness, or biological constraints on learning. (For recent reviews, see Domjan, 1983;Domjan & Galef, 1983;Johnston & Pietrewicz, 1985;LoLordo & Droungas, 1989;Ohman, 1986;Ohman, Dimberg, & 6st, 1985). However, because of the controversies generated by use of these frameworks, most contemporary research in this area has employed the more theoretically neutral term selective association.…”
mentioning
confidence: 99%
“…Taste obviously predicts the onset of gastric illness more reliably than flashing lights, after we have Garcia's result in hand. In response to this unsatisfying situation, several authors have argued that the study of preparedness needs a clear-cut predictive theory (3,18,19). Without such a predictive theory to guide them, investigators seem to have lost interest in further empirical studies of preparedness (see refs.…”
mentioning
confidence: 99%
“…However, various authors have shown that a reasonable rapprochement between the constraints of literature and process-oriented theory can be effected (e.g., Domjan & Galef 1983;Garcia & Holder 1985). It is quite possible that one or a small number of learning mechanisms serve a wide range of uses in different species.…”
Section: Donald a Dewsburymentioning
confidence: 99%